Peningkatan Kinerja Guru Melalui Supervisi Pendidikan Terhadap Guru MA Negeri 2 Serang Provinsi Banten - Andriwinata, Momon (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2023)
This research is motivated by the decline in teacher performance in the process of implementing teaching and learning. One of the indicators of decreased teacher performance in learning is the decreased learning achievement of students in the MA Nederi 2 Serang Banten Province. The purpose of this research is to improve teacher performance through individual supervision of teachers at MA Negeri 2 Serang Banten. The research method used is qualitative. Data collection techniques using interviews, observation and documentation studies. Based on the results of the research shows that; First, the implementation of student counseling services is carried out through the creation of a student counseling program and the formation of a student counseling team. Second, implementation of academic supervision through approaches and techniques; class visits, observe teacher performance, observe material management, lead group discussions. Third, monitor the results of teacher academic leadership by discussing learning methods, use and assessment techniques, use of learning environments, and use of study time.